A Wavelet-ADALINE Network Based Load Sharing and Control Algorithm for a FC/UC Hybrid Vehicular Power System - Ates, Y.; Uzunoglu, M.; Erdinc, O.; Vural, B. (IEEE, 2009)
The most attractive features of fuel cell technologies are the environment friendly operation and fuel economy. Instead of using only a FC system for vehicle propulsion, hybridizing FC system with an energy, storage system provides many advantages. Fuel cell (FC) and ultra-capacitor (UC) based hybrid power systems appear to be very promising for satisfying high energy and high power requirements for vehicular applications. In this study. an adaptive linear neuron (ADALINE) network and wavelet transform based energy management strategy developed for a FC/UC hybrid vehicle system is proposed. While wavelet transforms are suitable for analvzing and evaluating the dynamic load demand profile of a hybrid electric vehicle (HEV), the use of adaline network controller is appropriate for the hybrid system control. The mathematical and electrical models of the system are developed in detail and simulated using Matlat (R), Simulink (R) and SimPowerSystems (R) environments.
Keywords: ADALINE; Fuel cell; Hybrid Electrical Vehicle; Ultra-capacitor; Wavelet Transform; MANAGEMENT; Engineering